Investigation of effect of vehicle grilles on aerodynamic energy loss and drag coefficient - Yıldız, Ahmet; Dandıl, Beşir (Erol KURT, 2018)
In this study, the effects of grilles in a vehicle on the aerodynamic drag coefficient and energy loss have been investigated. For this purpose, grilles have been placed horizontally to the front of the vehicle. Firstly, the aerodynamic drag coefficient and aerodynamic energy loss of the vehicle model without grilles have been determined numerically. Then, the aerodynamic loss coefficient and the aerodynamic energy loss of the vehicle model with grilles have been determined. Thus, the effect of the grilles placed in the front of vehicle on aerodynamic resistance and energy loss is compared to the vehicle model without grilles. For all estimates, the vehicle models have been modeled in SolidWorks software. ANSYS-Fluent software has been used for numerical analysis for the modeled vehicles. It has been determined that the grilles placed in the front of vehicle increased the aerodynamic drag coefficient of the vehicle and thus the aerodynamic energy loss of the vehicle increased. Thus, it has been shown that it is possible to reduce a certain extent the additional aerodynamic losses in the vehicle by approaching the grilles designs closer to the vehicle model without grilles.